Dual vs. isolated anti-Ro antibody positivity in rheumatoid arthritis - Ma, Yan; Gu, Chaoyu; Li, Qianqian; Lu, Liangjing (Frontiers in Immunology, 2025)
ObjectiveThis study aimed to evaluate the clinical and immunological significance of anti-Ro52/TRIM21 and anti-Ro60/SSA antibodies in rheumatoid arthritis (RA), particularly the association of dual antibody positivity with disease severity, systemic manifestations, and therapeutic resistance.MethodsWe conducted a cohort study involving 670 RA patients, stratified into four groups according to anti-Ro52 and anti-Ro60 antibody status: Ro52+/Ro60+, Ro52+/Ro60−, Ro52−/Ro60+, and Ro52−/Ro60−. Clinical characteristics, disease activity scores (DAS28-ESR, DAS28-CRP), systemic complications, and treatment responses were compared among groups. Multivariate logistic regression models identified independent predictors of difficult-to-treat RA (D2T-RA).ResultsPatients with dual Ro52+/Ro60+ positivity exhibited significantly higher disease activity (median DAS28-ESR: 4.97 vs. 4.39, p = 0.002), worse functional status (median HAQ-DI: 0.88 vs. 0.63, p = 0.001), and increased systemic complications, notably interstitial lung disease (OR = 4.14, 95% CI: 1.71–10.68, p = 0.002) and hematologic involvement (OR = 2.50, 95% CI: 1.02–6.19, p = 0.044), compared to antibody-negative patients. Dual antibody positivity independently predicted an increased risk of developing D2T-RA (OR = 4.05, 95% CI: 1.58–11.09, p = 0.004). Conversely, patients with isolated Ro60 positivity exhibited lower IgG levels, fewer systemic complications, and reduced reliance on biological therapies, indicating a less severe disease phenotype.ConclusionAnti-Ro antibody subtyping effectively identifies distinct clinical and immunological RA subgroups. Patients with isolated Ro60 antibody positivity display a relatively less severe clinical profile compared to those with dual antibody positivity, highlighting the importance of specific antibody profiles in guiding personalized clinical management and therapeutic decision-making.